The Students’ Reading Competency on High Order Items in the Junior High School - Kusumadewi, Ni Wayan Eka; Tantra, Dewa Komang; Utami, I Gusti Ayu Lokita Purnamika (LPPM Undiksha, 2020)
This study aims to describe and compare the students’ reading competencies on high order items across classes, text genres, and reading indicators in SMPN 1 Ubud. The design implemented was descriptive and comparative research. The population of this research was the seventh grade students of SMPN 1 Ubud and the samples were four intact classes which determined through Cluster Random Sampling. The data were gathered by using Reading Competency Test. The collected data were then analysed descriptively and then inferentially by implementing a parametric statistics, namely: 1) central tendency measures, 2) measures of dispersion, and 3) simultaneous comparison. The result shows the students’ reading competency categorized as poor reading competency and there was not significance different in students’ reading competencies on high order thinking items across classes, text genres, and reading indicators. Poor reading competencies implies both of the students and EFL teachers to train intensively and extensively in reading process in order to have ability in determining the reading indicators of both descriptive and recount texts.